Students’ Perception on the Use of Note-taking Strategy in Listening - Episiasi, Episiasi; Wahidin, Wahidin; Suramto, Suramto; Kencana, Nila (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
Note-taking strategies are essential for students to understand the meaning of the conversations or audio files they hear. Therefore, the researchers conducted this study to find out how students perceive the use of note-taking strategies in listening process. This study was based on qualitative research. 24 students from an English Education department were selected to participate in this study. This study used questionnaires as a data collection technique. After data collection, the researchers conducted a descriptive analysis of the data following the process of reading or remembering, describing, and classifying. The results of this study indicate that students have a good awareness of using note-taking strategies in listening classroom. The students used note-taking strategies while listening to understand and remember each point of the information that was hear. It acts as a tool for developing working memory, focusing attention, and identifying important ideas within the information presented. The act of writing down information strengthens memory and helps students recall key details later. Students were focused on main points, paraphrase some ideas in their own words, and use symbols/color-coding to highlight important information in listening subject. Furthermore, using note-taking strategies in listening comprehension has many benefits, such as helping students retain information better, grasp key points, paraphrasing information, organizing notes with headings and lists, review previously learned material, and can improve students’ motivation, and increase students’ listening comprehension. As it is known that note taking can be a good strategy in learning due to its function and advantages in listening classroom.